Vzácné trombotické komplikace vyvolané vakcinací proti SARS-CoV-2 - Musil, Dalibor (Vnitrni lekarstvi, 2021)
Shortly after the worldwide initiation of vaccination against SARS-CoV-2, concerns emerged about a possible link between vaccination, severe thrombocytopenia, and the development of atypical venous thrombosis. Concerns were primarily about AstraZeneca (ChAdOx1 nCov-19), later Johnson & Johnson (Ad26.COV2.S), but cases of acute immune thrombocytopenic purpura (ITP) and bleeding without thrombosis and also atypical venous thrombosis after exposure to the messenger RNA-based vaccines produced by Pfizer-BioNTech and Moderna have been reported. Examination of the circumstances of these complications revealed that this is a similar mechanism to heparin-induced thrombocytopenia (HIT), a prothrombotic thrombocytopenic hypercoagulable disorder with venous and arterial thrombosis. HIT is caused by platelet-activating IgG antibodies directed against an antigen that is a macromolecular complex consisting of platelet factor 4 (PF4) and heparin. Naming this new entity vaccine-induced immune thrombotic thrombocytopenia (VITT) was suggested to avoid confusion with HIT. Patients had high levels of antibodies to the immune complex formed by PF 4 and the polyanionic component of the vaccine (double-stranded DNA). In patients with thrombosis at any vascular site after vaccination, accompanied by absolute or relative thrombocytopenia and systemic manifestations, HIT Ig ELISA assay to detect antibodies against PF4 and platelet-activating functional tests may be used for VITT recognition and differentiation from venous thromboembolic disease. Immune globulin impedes antibody-mediated platelet clearance and down-regulate platelet activation by immune complexes, as in HIT. It is prudent to choose from among the nonheparin antithrombotic agents - direct oral F.Xa inhibitors, direct thrombin inhibitors and indirect F.Xa inhibitors for the treatment of thrombosis.
Keywords: trombocytopenie; COVID-19; platelet factor 4; Ad26COVS1; Immunoglobulin G; Humans; atypical venous thrombosis; Platelet Factor 4; ChAdOx1 nCoV-19; portal venous thrombosis; Thrombocytopenia; vakcína Janssen proti COVID-19; vakcíny; PF4 platelet activation functional test; cerebral venous thrombosis; Vaccines; COVID-19 Vaccines; PF4-ELISA HIT assay; vaccine-induced immune thrombotic thrombocytopenia (VITT); imunoglobulin G; Purpura, Thrombocytopenic, Idiopathic; vakcíny proti COVID-19; Thrombosis; lidé; SARS-CoV-2; Vaccination; idiopatická trombocytopenická purpura; trombóza; trombocytový faktor 4; vakcinace; heparin-induced thrombocytopenia (HIT)